Obesogenic television food advertising to children in Malaysia: sociocultural variations - See H. Ng; Bridget Kelly; Chee H. Se; Karuthan Chinna; Mohd Jamil Sameeha; Shanhi Krishnasamy; Ismail MN; Tilakavati Karupaiah (Taylor & Francis Group, 2014)
Background: Food advertising on television (TV) is well known to influence children's purchasing requests and models negative food habits in Western countries. Advertising of unhealthy foods is a contributor to the obesogenic environment that is a key driver of rising rates of childhood obesity. Children in developing countries are more at risk of being targeted by such advertising, as there is a huge potential for market growth of unhealthy foods concomitant with poor regulatory infrastructure. Further, in developing countries with multi-ethnic societies, information is scarce on the nature of TV advertising targeting children. Objectives: To measure exposure and power of TV food marketing to children on popular multi-ethnic TV stations in Malaysia. Design: Ethnic-specific popular TV channels were identified using industry data. TV transmissions were recorded for each channel from November 2012 to August 2013 (16 hr/day) for randomly selected weekdays and weekend days during normal days and repeated during school holidays (n=88 days). Coded food/beverage advertisements were grouped into core (healthy), non-core (non-healthy), or miscellaneous (unclassified) food categories. Peak viewing time (PVT) and persuasive marketing techniques were identified. Results: Non-core foods were predominant in TV food advertising, and rates were greater during school holidays compared to normal days (3.51 vs 1.93 food ads/hr/channel, p<0.001). During normal days' PVT, the ratio of non-core to core food advertising was higher (3.25 food ads/hr/channel), and this more than trebled during school holidays to 10.25 food ads/hr/channel. Popular channels for Indian children had the lowest rate of food advertising relative to other ethnic groups. However, sugary drinks remained a popular non-core product advertised across all broadcast periods and channels. Notably, promotional characters doubled for non-core foods during school holidays compared to normal days (1.91 vs 0.93 food ads/hr/channel, p<0.001). Conclusions: This study highlights non-core food advertising, and predominantly sugary drinks are commonly screened on Malaysian TV channels. The majority of these sugary drinks were advertised by multinational companies, and this observation warrants regulatory attention.